A Surveillance study on the presence and safety of different types of food additive in children’s foods available in the markets - Izzat, Selar Sh. (Sulaimani Journal for Pure and Applied Sciences, 2017)
Health risk of food additives is under debates throughout the world. Several studies confirmed harmful effects and health problems associated with their consumption, but no data was published about this subject in Kurdistan and no awareness has been taken regarding this issue in the region. For this purpose 300 commercial food items consumed by children were collected from the markets and their labels analyzed for additive contents. As a result, 286 items (95.3%) found to contain additives, and only 14 (4.6%) were free from additive. The 286 items contained 120 different types of food additives and in 38 items (13.2%) the numbers and types of additives were not identified. From the 120 additive, 75 (62.5%) were found harmful, but no adverse effect found for 45 food additives (37.5%). The adverse health effects; 28 (23.3%) recorded as carcinogenic, 17 of them (14.4%) affected digestive as well as Respiratory Systems, and 15 of them (12.5%) were related to integumentary System problems. The most common additives found were color (27), followed by thickeners (25), and preservatives (12). The higher percentage of adverse effects for each of the color, thickener and acidity regulator were cancer-causing effects, however preservatives mostly affected the respiratory system. The more adverse health effects of additives related to color additives, and the higher percentage of color additive found in confectionery food items, so confectionery products were the more harmful food categories that children should avoid. Based on the results of this study, the quality of some food products meant for local markets is unsatisfactory. It needs to enforce and implement regulations on the manufacturers of products consumed by children to ensure the provision of excellent quality of products for the low-income population of the country.
Keywords: Food additive; Food color; INS; Preservatives